Virtual Reality and Biofeedback for Automotive Experience Assessment in Industry 5.0 - Brito, Gabriel de; Miguez, Rafael; Dias, Felipe Leão; Rodrigues, Daniela; Soussa, Márcio; Winkler, Ingrid (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais Estendidos do XXVI Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2024.244766, 2024)
In this session of XR Experience, we share our innovative industrial project that integrates biofeedback into a VR-based vehicle experience assessment carried out by the automotive industry. Our research group integrates Pico 4 Enterprise or Meta Quest Pro HMDs with Samsung 7 smartwatch, to showcase the analyses of participants’ heart rate and eye tracking data, offering insights into their stress levels, attention, and relaxation responses, surrogating their sense of presence in the immersive automotive experience.